1984
DOI: 10.3171/jns.1984.61.3.0515
|View full text |Cite
|
Sign up to set email alerts
|

The Dandy-Walker malformation

Abstract: Forty cases of Dandy-Walker malformation referred to the Hôpital Necker Enfants-Malades between 1969 and 1982 have been reviewed. The incidence of the malformation in hydrocephalus was 2.4%. There was a slight, statistically insignificant, female prevalence. Hydrocephalus should not be included in the definition of the syndrome. In 80% of the cases, it was actually a post-natal complication of the malformation and most often developed within 3 months after birth. In 80% of the cases, a communication, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
154
4
9

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(176 citation statements)
references
References 29 publications
9
154
4
9
Order By: Relevance
“…Psychomotor developmental delay and mental retardation have been mentioned frequently in DWM patients in the literature (7,8,9,10). Other psychiatric disorders accompanying this malformation have been rarely reported.…”
Section: In 1954mentioning
confidence: 96%
See 2 more Smart Citations
“…Psychomotor developmental delay and mental retardation have been mentioned frequently in DWM patients in the literature (7,8,9,10). Other psychiatric disorders accompanying this malformation have been rarely reported.…”
Section: In 1954mentioning
confidence: 96%
“…Although Hirsch et al (7) mentioned hydrocephalus as a frequent complication of DWM, they suggested that it is not necessary for the diagnosis.…”
Section: In 1954mentioning
confidence: 99%
See 1 more Smart Citation
“…The malformation occurs in approximately 1 per 25.000 live births, more frequently in girls than in boys (3). Usually, it is diagnosed in the prenatal period or early infancy, rarely in adulthood (3). Systemic anomalies in DWM may include cleft lip and palate, polydactyly, ORCID ID: orcid.org/0000-0003-0181-1166…”
Section: Introductionmentioning
confidence: 99%
“…Several other structured lesions of the central nervous system, such as cerebrovascular disease, brain stem tumors and Chiari malformation were described as mimicking MG, due to involvement or compression of the brain stem, could easily lead to misdiagnosis and an inappropriate treatment, but the DWS have not been reported to date 1,2,[6][7][8][9][10][11][12] .…”
mentioning
confidence: 99%